تطبيق الإصلاح في إدارة المعهد لتطوير بيئة اللغة العربية بالمعهد العصري مفتاح العلوم للمحمدية بكاجنجان بمنطقة بكالونجان - Jauhar Ali; Ayu Indah Lestari (Imtiyaz : Jurnal Pendidikan dan Bahasa Arab, 2021)
International Muhammadiyah Boarding School (IMBS) Pekajangan Pekalongan regency has implemented an Arabic language environment, but the environment has not developed well, because many teachers and students have not been consistent in using Arabic. The other reason is that IMBS Pekajangan Pekalongan has two management, namely management, namely school management and pesantren management. This research aims to find out how the implementation of changes in management of International Muhammadiyah Boarding School (IMBS) Pekajangan Pekalongan Regency in developing the Arabic language environment and what problems it faces and how the solution. This research uses a qualitative approach with this type of field research, and the analytical method is to select data, display data, conclude and investigate. The results showed that: 1.  The application of changes in pesantren management to develop the Arabic language environment at the International Muhammadiyah Boarding School (IMBS) Pekajangan Pekalongan Regency is in accordance with the correct theory. The proof is that  IMBS Pekajangan Pekalongan Regency  has succeeded in changing its management so that the Arabic language environment there has developed; 2. Problems in implementing management changes include:  a. Rejection from some teachers and employees at the International Muhammadiyah Boarding School (IMBS) Pekajangan Pekalongan Regency, b. The problem of lack of language mastery skills  Arab the teachers and principals themselves, c. Problems in choosing the right method in changing management; 3. Troubleshooting solution: a. All teachers and principals emphasize the importance of management changes to improve the quality of the institution, b. Provide an explanation of the benefits of management changes obtained by teachers and principals, c. Provide guidance and motivation to teachers that this management change will be easy if all elements of change, especially teachers, are against the planned policy, d. Pesantren administrators recruit teachers from pesantren graduates, especially those who have more skills in the field of Arabic, e. Provide Arabic vocabulary training to teachers and employees, f. Pesantren administrators conduct comparative studies to pesantren that have successfully implemented the Arabic environment, g. Consultation with pesantren leaders who have successfully implemented the Arabic language environment, h. Restrictions on interaction between students and teachers and employees who do not understand the language of Arab. This effort aims to minimize the use of Indonesian in everyday conversations.